Prevalence and Psychiatric Comorbidities of Internet Addiction in a Nationwide Sample of Korean Adults - Park, Subin (Psychiatry Investig, 2017)
The goal of the study was to examine the prevalence and psychiatric comorbidities of Internet addiction in a nationwide sample of Korean adults. Among a total of 6,022 participants involved in Korean Epidemiological Catchment Area study in 2011, 3,723 Internet users were assessed for their Internet addiction using Young's 8-item Diagnostic Questionnaire. The results showed that of the 3,723 Internet users, 39 (1.0%) had Internet addiction. Addicted Internet users were younger, more likely to be males and unemployed compared to non-addicted Internet users. Internet addiction was associated with alcohol and nicotine use disorders, depressive disorders, and anxiety disorder after controlling for age, gender, and occupational status. Internet addiction was associated with suicidal plans even after controlling for psychiatric disorders and socio-demographic factors. This study showed that Internet addiction is highly associated with variety of different psychiatric disorders and suicidal plans. Therefore, clinicians should carefully evaluate them when treating addicted Internet users.